CALCULATION METHODOLOGY FOR GEOMETRICAL CHARACTERISTICS OF THE FORMING TOOL FOR RIB COLD ROLLING - Olejnik, Andrej; Kapitanov, Alexey; Alexandrov, Islam; Tatarkanov, Aslan (Journal of Applied Engineering Science, 2020)
Calculation of the forming tool for rib cold rolling by the enveloping method is usually complex and very time-consuming. The cold rolling process is not always optimized, resulting in a poor quality of the rolled rib profile and premature failure of the forming tool. Improvement in techniques of rib rolling on metal heat-exchange tubes is a challenging technological task which has defined the purpose of the present work – the study of the effect of the forming tool for cold rolling of ribs by enveloping method on the accuracy of geometrical dimensions of ribbed surfaces. Absence of a well-developed calculation methodology for this type of tool at the present time adversely affects the rate of manufacturing application of rib cold rolling processes. Since the main task when introducing the rib rolling process is to achieve the required accuracy of the workpiece, it seems expedient to improve calculation methodologies allowing to design a forming tool for rib cold rolling taking into account the required accuracy of geometrical dimensions of the ribbed surfaces. The present work proposes a methodology that allows you to perform calculations of parameters required for manufacturing and supervision over various rolling tools. Experimental approbation data of the outlined methodology results are presented. As a result of deformation processing without additional technological operations, the effect of surface hardening has been achieved, and the roughness of rolled ribbed surfaces Ra was 0.8 μm, which is comparable in quality only with finishing machining. It was demonstrated that when calculating the coordinates of profile points, the geometry of the lead-in, as well as rolls with a screw rib, it is particularly important to determine the angle of crush forming rolls and the y-coordinate of rolling bars as the main characteristics of the profile.
Keywords: Ribbed surfaces, calculation methodology, forming tool, cold rolling, enveloping method